(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2007)
Present investigation was to develop novel ointment formulation in combination of natural wound healing agent curcuma longa, which is reported to possess wound healing and anti-bacterial activities. Combination of neomycin sulphate and curcuma longa is good rational, where curcuma longa produces synergistic wound healing effect with neomycin sulphate. Formulations containing fixed concentration (0.5 %) of neomycin sulphate and 3 %, 4 % and 5 % of curcuma longa were prepared. To assess the efficacy of formulations anti-bacterial activity, rheology, stability, spreadability and other physical characteristics were evaluated. The results obtained were encouraging and formulation containing neomycin sulphate (0.5 %) with 5 % of curcuma longa was found better than other formulations.